Analysis of The Mediating Role of Organizational Culture In Linking Competence and Discipline To Work Effectiveness: A Study of Creative Kokedama SMEs in Batu - Asep Dana Saputra; Sudarmiatin Sudarmiatin; Heri Pratikto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the impact of competence and discipline on employee performance through the mediating role of work culture at Creative Kokedama Batu. Using path analysis on 50 samples, the data indicate that competence and work discipline are crucial foundations for establishing a solid organizational work culture. Notable findings reveal that competence exerts a more significant influence than discipline, both in shaping work culture and in directly enhancing performance. Overall, the integration of competence, discipline, and work culture has been proven to significantly boost employee performance. The role of work culture as a mediator has also been confirmed to maximize the impact of competence on work outcomes. Therefore, human resource development strategies at Creative Kokedama Batu should prioritize enhancing competence to achieve optimal organizational performance.